Latanoprostene Bunod 0.024% versus Timolol Maleate 0.5% in Subjects with Open-Angle Glaucoma or Ocular Hypertension: The APOLLO Study - Weinreb, Robert N; Scassellati Sforzolini, Baldo; Vittitow, Jason; Liebmann, Jeffrey (Ophthalmology (Rochester, Minn.), 2016)
To compare the diurnal intraocular pressure (IOP)-lowering effect of latanoprostene bunod (LBN) ophthalmic solution 0.024% every evening (qpm) with timolol maleate 0.5% twice daily (BID) in subjects with open-angle glaucoma (OAG) or ocular hypertension (OHT). Phase 3, randomized, controlled, multicenter, double-masked, parallel-group clinical study. Subjects aged ≥18 years with a diagnosis of OAG or OHT in 1 or both eyes. Subjects were randomized (2:1) to a 3-month regimen of LBN 0.024% qpm or timolol 0.5% 1 drop BID. Intraocular pressure was measured at 8 am, 12 pm, and 4 pm of each postrandomization visit (week 2, week 6, and month 3). Adverse events were recorded throughout the study. The primary efficacy end point was IOP in the study eye measured at each of the 9 assessment time points. Secondary efficacy end points included the proportion of subjects with IOP ≤18 mmHg consistently at all 9 time points and the proportion of subjects with IOP reduction ≥25% consistently at all 9 time points. Of 420 subjects randomized, 387 completed the study (LBN 0.024%, n = 264; timolol 0.5%, n = 123). At all 9 time points, the mean IOP in the study eye was significantly lower in the LBN 0.024% group than in the timolol 0.5% group (P ≤ 0.002). At all 9 time points, the percentage of subjects with mean IOP ≤18 mmHg and the percentage with IOP reduction ≥25% were significantly higher in the LBN 0.024% group versus the timolol 0.5% group (mean IOP ≤18 mmHg: 22.9% vs. 11.3%, P = 0.005; IOP reduction ≥25%: 34.9% vs. 19.5%, P = 0.001). Adverse events were similar in both treatment groups. In this phase 3 study, LBN 0.024% qpm demonstrated significantly greater IOP lowering than timolol 0.5% BID throughout the day over 3 months of treatment. Latanoprostene bunod 0.024% was effective and safe in these adults with OAG or OHT.